(untitled) - Remmen, Arne (Denmark, 2003)
The booklet is aimed at enterprises, regardless of their sector or size, which are interested in reducing the environmental impact of their products. The focus is on a straightforward approach to environmental initiatives,...
Keywords: Environmentalism,Environmental protection,Môi trường học